2017
DOI: 10.1093/ntr/ntx272
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless Tobacco Use is “Replacing” the Smoking Epidemic in the South-East Asia Region

Abstract: It has been documented that the smoking prevalence has been declining in most countries of the South-East Asia region where effective anti-tobacco laws have been implemented. But due to a number of factors, the prevalence of smokeless tobacco has been increasing steadily, making the entire anti-tobacco movement less effective in terms of reducing the tobacco-attributable disease burden. In this context, this study has provided a detailed comparative analysis of the prevalence of smokeless tobacco use and smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 11 publications
4
48
1
Order By: Relevance
“…[2,3] Manufactured cigarettes are the most common type of tobacco consumed worldwide but other forms of tobacco such as chewing tobacco in South Asia and shisha smoking (waterpipe) in the Middle East are also quite common in these particular regions. [4,5] Smokeless tobacco (SLT) is also a major risk factor for oropharyngeal cancer as well as increased risk of heart disease. [6,7] South Asians, estimated at one quarter of the world's population, represent one of the highest proportions of the global population that are affected by current and future disease burden due to tobacco consumption.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Manufactured cigarettes are the most common type of tobacco consumed worldwide but other forms of tobacco such as chewing tobacco in South Asia and shisha smoking (waterpipe) in the Middle East are also quite common in these particular regions. [4,5] Smokeless tobacco (SLT) is also a major risk factor for oropharyngeal cancer as well as increased risk of heart disease. [6,7] South Asians, estimated at one quarter of the world's population, represent one of the highest proportions of the global population that are affected by current and future disease burden due to tobacco consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The paucity of research and dearth of adequate evidence base on the extent of problem and harmful effects of SLT lead to barriers in effective implementation of SLT control measures by the interested stakeholders 9 . A recent study by Suliankatchi et al 10 reported a shift in the preference of tobacco users from smoking to SLT use in SEAR countries including Bangladesh, India and Nepal. It has been shown that users who start with low-nicotine ‘starter’ products are likely to subsequently ‘graduate’ to products with higher-nicotine content 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a misleading advertising by tobacco companies may be responsible for the increase in the SLT prevalence, which is as harmful as smoking (Suliankatchi et al, 2019). Use of smokeless tobacco leads to potentially preventable, global morbidity and mortality diseases.…”
Section: Quantification Of Nicotine and Cotinine In Plasma Saliva Amentioning
confidence: 99%